(untitled) - Trebilcock, M. J. (New York, 1995)
Drawing on previous highly praised editions this comprehensive text is an invaluable guide to students of economics, law, politics and international relations. Now fully updated, this third edition includes full coverage of new developments including the Doha trade round, attitudes towards the Kyoto protocol and the growing body of WTO dispute resolution case law.
Keywords: Foreign trade regulation,Quy định thương mại nước ngoài.